Peruvian Education at a Crossroads : Challenges and Opportunities for the 21st Century - World Bank (Washington, DC, 2013)
Peru has reached a crossroads for education policy at the beginning of the 21st century. The status quo reflects major accomplishments. One direction for policy would, therefore, involve useful but relatively limited improvements in the current situation. This direction, however, may prove inadequate to fulfill the country's goal of having a highly educated citizenry--fully competitive by international standards--to underpin poverty reduction and to facilitate economic and social development. A second generation of reform would be required if this direction were taken. This study explores these issues and lays out options for a second wave of reform. Either of the broad directions for policy will need to identify specific ways of improving educational quality. This report analyzed the factors affecting fourth graders' mathematics achievement levels in 1996 to identify options to improve quality. The findings are encouraging in indicating potential directions where change could make a difference. The analysis found that after controlling for a number of explanatory variables, the performance of poor and extremely poor departments was better than non-poor departments of education. To level the playing field for all Peruvian children, then, it is necessary to improve equity, quality, and efficiency in planning and policy.